Peningkatan Digitalisasi UMKM Desa Bandar Khalipah melalui QRIS, Penandaan Lokasi Usaha di Google Maps, dan Penguatan Promosi VIsual dalam KKN UINSU 2025 - Elysia, Nurul Syaadah; Pratiwi, Dea Indah; Sari, Seva Maya (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to enhance the digitalization of MSMEs in Bandar Khalipah Village through the implementation of QRIS, business location mapping on Google Maps, and the strengthening of visual promotion. The main problems faced by MSMEs include low digital literacy, limited access to cashless payment systems, and suboptimal business identity and promotional materials. The program was carried out through observation, training, and direct assistance to business owners in Bandar Khalipah Village. The results show that most MSMEs successfully activated QRIS, registered their business locations on Google Maps, and obtained more attractive visual promotional materials. This program has proven to improve transaction efficiency, business visibility, and marketing appeal. These findings underline the importance of digitalization as a strategy for empowering MSMEs to enhance competitiveness and business sustainability.